Inhibition of Col6a5 Improve Lipid Metabolism Disorder in Dihydrotestosterone-Induced Hyperandrogenic Mice - Sun, Li-Feng; Yang, Ya-Li; Wang, Mei-Yue; Zhao, Hua-Shan; Xiao, Tian-xia; Li, Meng-Xia; Wang, Bao-Bei; Huang, Chen; Ren, Pei-Gen; Zhang, Jian V. (Frontiers in Cell and Developmental Biology, 2021)
Hyperandrogenism is a key pathological feature of polycystic ovarian syndrome (PCOS). Excess androgen can lead to PCOS-like cell hypertrophy in the ovaries and adipose tissue of rodents. Here, we established a dihydrotestosterone (DHT)-induced hyperandrogenic mouse model to analyze the differences in gene expression and signaling pathways of the ovaries and gonad fat pads of mice treated with or without DHT by RNA microarray analysis. From the results, we focused on the overlapping differentially expressed gene—Col6a5—and the major differentially enriched signaling pathway—lipid metabolism. We employed DHT-induced ovarian interstitial cell, adipogenic 3T3-L1 cell and NCTC1469 cell models to investigate whether androgens directly mediate lipid accumulation and hypertrophy. We found that DHT increased lipid droplet accumulation in ovarian interstitial cells and adipogenic 3T3-L1 cells but not NCTC1469 cells. DHT significantly altered interstitial cell cholesterol metabolism, as indicated by changes in cholesterol levels and the expression of related genes, but these effects were not observed in 3T3-L1 cells. Moreover, Col6a5 expression was significantly increased in ovaries and gonadal fat pads of DHT-treated mice, and Col6a5 inhibition alleviated DHT-induced excess lipid accumulation and hypertrophy of ovarian interstitial cells and adipogenic 3T3-L1 cells, even improved lipid metabolism in overnourished NCTC1469 cells. Our results indicate that Col6a5 plays important roles in the pathogenesis of DHT-induced lipid metabolism disorder and the hypertrophy of ovarian interstitial cells and adipocytes.